Neonatal sequential organ failure assessment score within 72 h after delivery reliably predicts bronchopulmonary dysplasia in very preterm infants - Xu, Doudou; Dong, Ziwei; Yin, Xiaoli; Yang, Yuanyuan; Wang, Yang (Frontiers in Pediatrics, 2023)
Background: The neonatal sequential organ failure assessment (nSOFA) score is an operational definition of organ dysfunction which was adapted to predict sepsis-associated mortality. However, the relationship between nSOFA score and BPD has not been investigated. The aim of this study was to evaluate whether the nSOFA score within 72 h after delivery could be used to predict the occurrence of BPD in very preterm infants. Methods: We performed a retrospective, single-center cohort study of preterm infants from 2019 to 2021. The nSOFA score was calculated from medical records after admission to the neonatal intensive care unit (NICU) in the first 72 h after delivery and the peak value was used for calculation. Logistic regression models were used to evaluate the relationship between the nSOFA score and BPD. Propensity score matched and subgroup analysis were used to verify the reliability of the results. Results: Of the 238 infants who met inclusion criteria, 93 infants (39.1%) with BPD. The receiver operating characteristic curve (AUROC) for the nSOFA score to predict BPD was 0.790(95% CI:0.731-0.849). Logistic regression models showed that each unit increase in the nSOFA score correlated with a 2.09-fold increase in the odds of BPD (95% CI: 1.57-2.76) and 6.36-fold increase when the nSOFA score is higher than 1.5 (95% CI:2.73-14.79). Conclusions: The nSOFA score within 72 h after delivery was independently correlated with BPD, Which suggested that it can be a useful tool for clinicians to accurately identify high risk infants and implement early intervention.